Platanus-allee is a de novo haplotype assembler enabling a comprehensive access to divergent heterozygous regions - Rei Kajitani (Nature Portfolio, 2019)
Most phasing programmes for sequencing data work well for genomes with low heterozygosity but drop in performance in regions of high heterozygosity. Here, Kajitani et al. develop the assembler Platanus-allee and demonstrate its utility in de novo assemblies of various genomes and the human MHC region.